Smoke - Hopkins, Ellen (Burned, 2013)
After the death of her abusive father and loss of her beloved Ethan and their unborn child, Pattyn runs away, desperately seeking peace, as her younger sister, a sophomore in high school, also tries to put the pieces of her life back together.